2022
DOI: 10.1155/2022/8592729
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Study on Factors Associated with High Myopia CNV in Aqueous Humor and Serum

Abstract: Objective. The objective is to investigate the relationship and correlation between PEDF and TGF-β in aqueous humor and serum and high myopia CNV lesions. Methods. For each group of patients (namely, group A: patients with high myopia CNV (mCNV); group B: patients with high myopia without CNV; group C: patients with CNV caused by other eye diseases; and group D (control group): patients with simple cataract (without CNV and high myopia)), 20 patients were collected. A total of 40 patients have been collected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Myop CNV patogenezise nem teljesen ismert. Prekurzor lézió kialakulása indítja meg a folyamatot (hátsó pólus atrófia, elongáció), a pigment epithel -Bruch-membrán -choriocapillaris komplexben elváltozások jönnek létre (11). Choroidea erek mennyiségének relatív csökkenése és/vagy patológiás elváltozások kialakulása relatív hypoxiát eredményez a PE területén és a gliasejtekben, amelynek következtében a VEGF szintje megemelkedik (an-4.…”
Section: Klinikai Kutatásokunclassified
“…Myop CNV patogenezise nem teljesen ismert. Prekurzor lézió kialakulása indítja meg a folyamatot (hátsó pólus atrófia, elongáció), a pigment epithel -Bruch-membrán -choriocapillaris komplexben elváltozások jönnek létre (11). Choroidea erek mennyiségének relatív csökkenése és/vagy patológiás elváltozások kialakulása relatív hypoxiát eredményez a PE területén és a gliasejtekben, amelynek következtében a VEGF szintje megemelkedik (an-4.…”
Section: Klinikai Kutatásokunclassified
“…TGFβ expression can explain the epithelial to mesenchymal transition (EMT) and the expression of α-smooth muscle actin (α-SMA) as well as the scleral ECM makeover observed in LEC from myopic eyes [ 13 , 14 , 15 , 16 ]. Local (AH) and systemic (plasma) associations between the increased levels of TGF-βs, matrix metalloproteinase (MMP), and tissue inhibitors of MMP (TIMP) have been observed in myopic patients [ 15 , 17 , 18 , 19 ]. Other studies have confirmed TGFβ involvement in AH from high myopic patients and PEDF involvement in intraocular CNV lesions, but circulating TGFβ and PEDF had no significant correlation with high myopia or intraocular CNV disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding and edema caused by CNV are the common complications leading to visual function loss in patients with high myopia, which greatly reduces the vision-related quality of life of patients. Without treatment, the vision of most patients with high myopic CNV will further deteriorate and may lead to blindness [2] . The vascular endothelial growth factor A (VEGFA) secreted by retinal pigment epithelium cells (RPE), an important subtype of VEGF, is involved in the genesis and development of CNV [3] .…”
Section: Introductionmentioning
confidence: 99%